IMPLEMENTASI NASIHAT RASUL PAULUS TENTANG PERSEMBAHAN YANG BENAR BERDASARKAN ROMA 12:1- 3 BAGI JEMAAT GEREJA ISA ALMASIH SUKOREJO, KENDAL, JAWA TENGAH - Baene, Noferianus; Purwoko, Paulus Sentot; Hendrikus, Hendrikus (JURNAL KADESI, 2024)
A true offering is a gift to an honorable person. The word offering can also be interpreted as dedication, surrender, respect, devotion or asking for protection from someone who is considered stronger than oneself. When someone hands over an offering, it contains a confession that the Lord Jesus has looked after us faithfully and perfectly. A true offering should begin with the willingness to offer oneself and one's life completely to God, that is a living and holy offering. Along with this, when Christians attend or attend worship in the midst of church, apart from providing their hearts and minds to commune with God, people must also prepare offerings that will be submitted to God. This is also emphasized in Deuteronomy 16:16-17 where it says "God invites the people to appear before God, but not empty-handed. Therefore, this research aims to determine the level and dimension that most dominantly determines the implementation of the Apostle Paul's advice regarding Correct Offerings Based on Romans 12:1-3 for the congregation of the Church of Jesus Christ, Sukoerjo, Kendal, Central Java, namely offering the body. This research uses quantitative methods. This research uses quantitative methods. Data collection was obtained from observations and distributed questionnaires. The results of the level of implementation of the Apostle Paul's advice regarding correct offerings based on Romans 12:1-3 for the congregation of the Church of Jesus Christ in Sukorejo, Kendal, Central Java are in the medium category and the dominant dimension determining the implementation of the Apostle Paul's advice regarding correct offerings based on Romans 12:1 -3 For the congregation of the Church of Jesus Christ, Sukorejo, Kendal, Central Java, this is to present correct behavior.